Use of authentic material in virtual classrooms for learning a foreign language - Tolentino Quiñones, Hermis (2020)
The development of technology has allowed significant changes in education to take place today, so much so that, we talk about remote education, with more attention being paid to virtual classrooms, E-learning and B-learning as spaces where students and teachers can interact as it is done in the classroom. And this essay aims to reflect on the use of authentic material in virtual classrooms of languages as a foreign language (LE) in the E-learning and B-learning modality. In this context, authentic material plays an important role in the learning of a foreign language because it encourages the development of linguistic, sociocultural and pragmatic skills. In this sense, the objective of this essay is to reflect on the use of authentic material in virtual classrooms of languages as a foreign language (LE) in the E-learning and B-learning modality. For this reason, in this essay, a conceptualization of the presented arguments was made, identifying qualities, advantages, challenges, and implications in the glottodidactic. In this sense, after the reviewing, analyzing and reflecting about the theory it was concluded that the use of virtual classroom and authentic material in the learning of a foreign language is important and for that reason language teachers are encouraged to use them according to the realities and student needs.